Trophic relationships in orchid mycorrhiza – diversity and implications for conservation - Rasmussen, Hanne; Rasmussen, Finn (Lankesteriana: International Journal on Orchidology, 2015)
Orchid species are perennial, and though demo- graphic data suggest that the family includes r- as well as K-strategists (Whigham & Willems 2003), most species are potentially long-lived. Individual plants may be kept in living plant collections or in nature reserves for practically unlimited periods of time. There are several reports on natural populations suspected of little or no seedling recruitment, “senile populations” (Tamm 1991, Rasmussen 1995), espe- cially among rare orchids under critical surveyance. Such populations may function as a seed source to neighbouring areas but are likely to eventually disap- pear from the site.